Family, human communication and systemic approach in their relation with schizophrenia - Lilian Acevedo Sierra; Ernesto Hermilio Vidal López (Centro Provincial de Información de Ciencias Médicas, 2019)
For the theoretical and practical analysis of the family it is necessary to know its way of functioning, the system concept and its different theories, communication as main element in all social group and the particularities of double binding in those with a schizophrenic member, since generally they show problems in communication, not only from the sick person's behavior, but also from the other family members behavior. In that sense, a literature review related to the topic was carried out which allows the selection of the systemic approach for the implementation in the daily practice.